GEOSPATIAL ANALYSIS OF THE RELATIONSHIP BETWEEN URBAN STRUCTURE, VEGETATION, POPULATION AND SURFACE TEMPERATURE IN THE CUIABÁ-VÁRZEA GRANDE-MT CONURBATION - Dias, Bruna Aparecida Silva; Silva, João Paulo da; Santos, Natália de Souza; Colin, Carolina Garcia de Figueiredo; Figueiredo, Vera Aparecida de; Chaves, Jean Victor Barrozo; Barbosa, Luiz Antônio Falaguasta; Antônio Speranza, Eduardo; Silva, João dos Santos Vila da (Ra'e Ga: o Espaço Geográfico em Análise, 2025)
The urbanization process does not occur in a synchronized way, which could result in differences of urban areas depending on various socioeconomic factors. The implications of such differences can result in long-term consequences for the local urban context. This study proposes a descriptive model to characterize the Cuiabá–Várzea Grande (Mato Grosso State) conurbation, considering its building structure, vegetation cover, land surface temperature, population, and topography. To accomplish this, spectral indices derived from remote sensing data, related to built-up areas, vegetation, and land surface temperature were employed, along with terrain elevation and population information from census data. The model, based on cluster analysis, allowed the identification of three units which explain the urban distribution of the conurbation: two strongly associated with the building structure (more or less densely built up) and a third one with mainly vegetation cover, generally located at the edges of the study area. These characteristics are reflected in land surface temperature, which is lower in the unit with a higher presence of green cover and higher in the area with dense constructions and scarce vegetation. The unit encompassing the central regions has open areas that could be used for more efficient uses, such as commercial, residential, or social activities. The proposed model demonstrates the potential to improve the management of the urban development in the area under study.